Reliable identification and quantification of neural cells in microscopic images of neurospheres. Issue 5 (19th November 2021) - Förster, Nils; Butke, Joshua; Keßel, Hagen Eike; Bendt, Farina; Pahl, Melanie; Li, Lu; Fan, Xiaohui; Leung, Ping‐chung; Klose, Jördis; Masjosthusmann, Stefan; Fritsche, Ellen; Mosig, Axel
Abstract: Neurosphere cultures consisting of primary human neural stem/progenitor cells (hNPC) are used for studying the effects of substances on early neurodevelopmental processes in vitro. Differentiating hNPCs migrate and differentiate into radial glia, neurons, astrocytes, and oligodendrocytes upon plating on a suitable extracellular matrix and thus model processes of early neural development. In order to characterize alterations in hNPC development, it is thus an essential task to reliably identify the cell type of each migrated cell in the migration area of a neurosphere. To this end, we introduce and validate a deep learning approach for identifying and quantifying cell types in microscopic images of differentiated hNPC. As we demonstrate, our approach performs with high accuracy and is robust against typical potential confounders. We demonstrate that our deep learning approach reproduces the dose responses of well‐established developmental neurotoxic compounds and controls, indicating its potential in medium or high throughput in vitro screening studies. Hence, our approach can be used for studying compound effects on neural differentiation processes in an automated and unbiased process.